Little pro’s, but how many of them? – On 3SG null pronominals in Hungarian - Dalmi, Gréte (LingBaW. Linguistics Beyond and Within, 2017)
While Hungarian 3SG individual reference null pronominals are in free variation with their lexical counterparts, 3SG generic reference null pronominals do not show such variation. This follows from the fact that Hungarian 3SG generic null pronominals behave like bound variables, i.e. they always require a 3SG generic lexical antecedent in an adjacent clause. Both the 3SG generic lexical antecedent and the 3SG generic null pronominal must be in the scope of the GN operator, which is seated in SpeechActParticipantPhrase (SAPP), the leftmost functional projection of the left periphery in the sentence (see Alexiadou & D’Alessandro, 2003; Bianchi, 2006). GN binds all occurrences of the generic variable in accessible worlds (see Moltmann 2006 for English one/oneself). These properties distinguish Hungarian from the four major types of Null Subject Languages identified by Roberts & Holmberg (2010).